Aspergillus oryzae Fermented Plumula Nelumbinis Against Atopic Dermatitis Through AKT/mTOR and Jun Pathways - Fengfeng Chen; Jing Liu; Xinwei Yu; Honglei Jia; Cheng Yang; Bingtian Zhao (Pharmaceuticals)
Background/Objectives: Atopic dermatitis (AD) is a chronic inflammatory skin disorder that has attracted global attention, and alkaloids from Plumula Nelumbinis have been shown to have anti-inflammatory activity. Fermentation has been used for the structural modification of natural compounds to improve bioavailability and activity, but the AD therapeutic efficacy and mechanism of the fermented Plumula Nelumbinis (FPN) are still unclear. Methods: The potential targets of FPN for AD were preliminarily screened using network pharmacology, and then PCR and WB were used to prove the therapeutic effect of FPN in AD. Results: Network pharmacology indicated that mTOR and Jun were key targets for AD. The experiments in vitro showed that FPN could effectively block AKT/mTOR and AKT/Jun-mediated inflammatory signaling pathways. Moreover, FPN can also alleviate SDS-induced inflammation in zebrafish. It is also found that the anti-inflammatory activity of Plumula Nelumbinis was enhanced by Aspergillus oryzae fermentation, and the oil phase of the fermentation product showed better activity, which may be due to microbial fermentation changing the structure of the original alkaloids. Conclusions: This study elucidated the potential mechanisms of alkaloids derived from fermented Plumula Nelumbinis against AD; it may also provide a scientific basis for the development of new drugs for AD.